Dosis de lixiviado de humus de lombriz en el crecimiento y rendimiento del forraje hidropónico de Zea mays L. maíz duro. Loreto - Diaz Gonzales, Roy Rodrigo (2025)
The present study evaluated the economic profitability of hydroponic green forage production of maize with water and probiotic in Zúngarococha in 2023. Using an experimental design, two groups were compared: one treated with a probiotic and one without, distributed in 98 trays within a controlled hydroponic system. The variables measured included plant height, stem diameter, number of leaves, and yield in both fresh and dry matter. The results showed that, although the use of probiotics increases the agronomic yield of corn, it does not necessarily translate into a higher economic profitability. This is due to the costs associated with probiotics. The ANOVA statistical analysis confirmed significant improvements in the growth of plants treated with probiotics compared to the control group. In conclusion, although the use of probiotics in hydroponic corn cultivation improves certain growth parameters, its economic profitability is limited by the high initial costs. It is suggested that more research be carried out to explore different concentrations of probiotics and their long-term effects, as well as consider cost reduction to improve the economic viability of this agricultural technique